Intermolecular interactions and structural organization of a native chitin-chitosan hydrocolloid network resolved by solid-state NMR and molecular dynamics - Qinghui Cheng; Chunyan Lu; Xiufang Gong; Qingyan Wang; Siming Liao; Lihua Chen (Food Hydrocolloids, 2026)

Electrically enhanced, Nature-Driven microbial attenuation of chromate and dichloromethane in groundwater - Qingxia Li; Qinghao Zhang; Dandan Huang; Siming Chen; Baogang Zhang (Bioresource Technology, 2026)

Ultrasound-assisted complexation of Millettia speciosa by-product protein with polyphenols: improved structural properties, antioxidant and hypoglycemic activities, and gut microbiota modulation - Meng Wang; Jiexi Li; Feng Li; Yebao Chen; Fangfang Ban; Hua Yang; Siming Zhu; Dan Xu; Junlin Wu (Food Chemistry, 2026)

Corrigendum to “Electrically enhanced, Nature-Driven microbial attenuation of chromate and dichloromethane in groundwater” [Bioresour. Technol. 459 (2026) 135175] - Qingxia Li; Qinghao Zhang; Dandan Huang; Siming Chen; Baogang Zhang (Bioresource Technology, 2026)

A hierarchical hybrid flood modeling framework: deconstructing runoff response into initiation states and generation processes - Tao Xie; Lu Chen; Bin Yi; Zhiyuan Leng; Siming Li; Yazhong Wu; Deming Zhu (Journal of Hydrology, 2026)

Corrigendum to “A flood peak prediction in data-scarce mountain river basins considering the time distribution of rainfall” [J. Hydrol. 673 (2026) 135352] - Siming Li; Lu Chen; Binlin Yang; Bin Yi; Zhiyuan Leng; Tao Xie; Yang Song (Journal of Hydrology, 2026)

Comprehensive Transcriptomic and Proteomic Profiling of CILD40 with Novel Compound Heterozygous Mutations of DNAH9 - Siming Kong; Mingshuo Wang; Xuedong Wang; Yakun Liu; Pengfei Wang; Wenyan Song; Ziye Chen; Yuxin Su; Canhong Xiang; Yunfang Wang; Hui Bai (Phenomics, 2026)
Primary ciliary dyskinesia (PCD) is a rare genetic disorder characterized by impaired ciliary motility that leads to respiratory symptoms, laterality defects, and other systemic abnormalities. Despite significant advancements in genetic research identifying over 50 causative genes and enabling genetic diagnosis in approximately 90% of cases, comprehensive phenotypic characterization remains underexplored. We investigated two respiratory asymptomatic individuals (sisters) who exhibited laterality defects in a three-generation family, both of whom harbored novel compound heterozygous mutations (NM_001372.4:c.308del and NM_001372.4:c.11845G > A) in the dynein axonemal heavy chain 9 ( DNAH9 ) gene associated with primary ciliary dyskinesia-40 (CILD40). Structural modeling and western blotting analysis of HEK-293T cells demonstrated that the frameshift mutation abolished DNAH9 stability, whereas the missense mutation disrupted hydrogen bonds, leading to partial protein destabilization. Peripheral blood RNA sequencing revealed extensive dysregulation of axonemal and intraflagellar transport genes, implicating defects in microtubule-based motility in the two affected siblings with biallelic DNAH9 mutations, but not in their heterozygous family members or one unaffected relative. Plasma proteomic analysis of patients with CILD40 identified significant enrichment of pathways related to platelet activation, complement and coagulation cascades. Further comparative analysis with a patient with PCD caused by a CCDC40 mutation (CILD15 subtype) revealed differential signatures in CILD40, highlighting the potential of plasma proteomics for understanding distinct pathogenic mechanisms across PCD subtypes. These findings underscore the critical role of DNAH9 compound heterozygous mutations in CILD40 and provide new insights into the genetic, transcriptional, and proteomic phenotypic heterogeneity of PCD.

A flood peak prediction in data-scarce mountain river basins considering the time distribution of rainfall - Siming Li; Lu Chen; Binlin Yang; Bin Yi; Zhiyuan Leng; Tao Xie; Yang Song (Journal of Hydrology, 2026)

Increased microbiological risks caused by extreme precipitation in a drinking water system in mountainous area: From source to tap - Xinyan Xiao; Chen Cheng; Xiuxiu Wang; Ziqi Luo; Lihua Li; Siming Hu; Dongmei Zhu; Mingbao Feng; Chengsong Ye; Xin Yu (Journal of Hazardous Materials, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Screening and characterization of microbial consortia for biodegradation of high-salt and high-oil food waste - Meng Wang; Lirong Xia; Minghui Yang; Hua Yang; Zhongsheng Tang; Yebao Chen; Siming Zhu; Junlin Wu (Waste Disposal & Sustainable Energy, 2026)

Multi-level magma reservoir and open system processes of the Tianchi caldera, Changbaishan Volcanic Field, NE China - Siming Chen; Tong Hou; Ronghao Pan; Diao Luo; Guoming Liu; Roman Botcharnikov (Journal of Volcanology and Geothermal Research, 2026)

Non-thermal processing of Citrus reticulata cv. Chachiensis pulp: Antioxidant screening and mechanism in Caenorhabditis elegans based on transcriptomics and metabolomics - Quancen Lee; Siming Zhu; Ping Chen; Yutao Wang; Liang Chen; Zhendong Wang (Food Bioscience, 2026)

Fine-scale mangrove species monitoring and ecological threshold assessment for coastal management in Quanzhou Bay, China - Siming Chen; Fei Chen; Longhui Niu; Zhong Deng; Kebin Wu; Wenbin Li (Environmental Monitoring and Assessment, 2026)

Berberine inhibits ISG15 and pyroptosis to attenuate diabetic kidney disease inflammation and fibrosis - Lingzhi Huang; Qinqin Chen; Xiaoxiao Liu; Liuqing Wang; Xingyue Liao; Siming Yuan; Liqin Tang (Apoptosis, 2026)

Okadaic acid induces oxidative stress and immunotoxicity in zebrafish: involvement of the p53 pathway and behavioral alterations - Duo Chen; Siming Pan; Jiapeng Wang; Zhenlu Li; Chenhuan Dong; Yuanxin Liang; Yilin Huang; Youqiang Chen; Ting Xue; Chentao Lin (Fish & Shellfish Immunology, 2026)

Revealing long-term runoff mechanisms using the deep learning model interpretable framework driven by global and local information - Binlin Yang; Lu Chen; Siming Li; Bin Yi; Nengjie Hu (Journal of Hydrology, 2025)

Microbial electrochemical reduction of chromate in groundwater driven by Thiobacillus denitrificans - Luyao Wang; Siming Chen; Song Wang; Xinxin Li; Baogang Zhang (Journal of Environmental Chemical Engineering, 2025)

Cellulose-engineered janus periosteum with compartmentalized angiogenic and osteo-immunomodulatory abilities for bone regeneration - Wuyan Xu; Kun Liu; Jiaqing Chen; Junliang Liu; Siming Li; Hua Wang; Binghong Luo; Qingqi Meng (Carbohydrate Polymers, 2025)

Methionine in embryonic development: metabolism, redox homeostasis, epigenetic modification and signaling pathway - Chang Yan; Biyan He; Chenjun Wang; Wanzhen Li; Siming Tao; Jingqing Chen; Yuquan Wang; Ling Yang; Yingjie Wu; Zhenlong Wu; Ning Liu; Yinghe Qin (Critical Reviews in Food Science and Nutrition, 2025)

Interaction mechanism and structure-activity relationship of hesperidin, methyl hesperidin and hesperidin methyl chalcone with ovalbumin: A comparative study - Xuefei Wen; Xinpeng Li; Siming Zhu; Liang Chen; Zhendong Wang; Ming Yu; Zhanhua Deng (Food Chemistry, 2025)

Structural insights into polysaccharides in Ganoderma lucidum cell walls by solid-state NMR - Lihua Chen; Siming Liao; Qinghui Cheng (Carbohydrate Polymers, 2025)

A Dynamic Time-varying Distributed Unit Hydrograph Considering the Heterogeneity of Runoff Generation - Bin Yi; Lu Chen; Binlin Yang; Zhiyuan Leng; Siming Li; Tao Xie (Water Resources Management, 2025)

Bibliometric and visual analysis of drug-specific immunotherapy from 1990 to 2024 - Zhengjiu Cui; Xiaorui Chen; Siming Zhai; Yuanyuan Wang; Chanchan Hu; Bin Yuan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Novel metabolic pathways of bioelectrochemical vanadate reduction by Thiobacillus denitrificans without exogenous electron donor supplementation in groundwater - Luyao Wang; Siming Chen; Rui Li; Baogang Zhang (Water Research, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Catalytic-difference elucidating of hesperidin and naringin by Rhamnosidase and prunin production enhancing through enzyme mutation - Xinpeng Li; Ping Chen; Lin Chen; Sheng Gao; Zhendong Wang; Siming Zhu (Food Bioscience, 2025)

An integrated non-alkaline derivatization strategy using 2,2′-dithiodipyridine and HPLC for simultaneous analysis of total and low-molecular-weight free thiols in human serum - Zhiyu Shao; Jie Zeng; Jun Dong; Fusui Ji; Hongxia Li; Ruiyue Yang; Wenxiang Chen; Wenyu Li; Siming Wang (Analytica Chimica Acta, 2025)

Genetic analysis and fine mapping reveal that AhRt3, which encodes an anthocyanin reductase, is responsible for red testa in cultivated peanuts - Yanyan Tang; Xiantao Zhou; Xin Li; Cai Zhou; Wenlin Wang; Mo Zhou; Zhicheng Hu; Xiaobei Li; Kaiyuan Zhang; Siming Wang; Zhihao Zhang; Hao Chen; et al. (Theoretical and Applied Genetics, 2025)

Correction: Cinnamaldehyde Alleviates Alveolar Epithelial Cell Injury in ALI by Inhibiting the CaMKII Pathway - Lei Liu; Hao Zhang; Siming Chen; Wankang Dian; Zhou Zheng (Cell Biochemistry and Biophysics, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Integrative transcriptomic, proteomic and metabolomic analyses yields insights into muscle fiber type in cattle - Xiaofan Tan; Ruixue Zhao; Jing Chen; Zhiwei Yan; Xin Sui; Heling Li; Qiao Li; Xuehai Du; Yangzhi Liu; Siming Yao; Ying Yang; David M. Irwin; et al. (Food Chemistry, 2025)

Acetated starch inclusion to tailor the hierarchical structure and sol-gel features of middle gluten wheat starch-based binary matrices - Bowen Chen; Guojia Jin; Shengsong Ji; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Hydrocolloids, 2025)

Experimental Investigation of Seismic Signal Characteristics Arising from Basal Stress Fluctuations in Granular Flow - Xiao Yu; Zheng Chen; Siming He; Wei Liu; Dongpo Wang (Rock Mechanics and Rock Engineering, 2025)

Microplastics alter the migration and transformation of vanadium in the riverine sediment environment - Siming Chen; Xinyue Zhang; Luyao Wang; Cuibai Chen; Jiamin Huang; Baogang Zhang (Science of The Total Environment, 2024)

Untargeted metabolomics to detect and identify plasma metabolic signatures associated with intracranial aneurysm and its rupture - Siming Gui; Jia Jiang; Dingwei Deng; Dachao Wei; Xiheng Chen; Yudi Tang; Jian Lv; Wei You; Ting Chen; Yang Zhao; Hengwei Jin; Xinke Liu; et al. (Metabolic Brain Disease, 2024)

Evaluating the impact of improved filter-wrapper input variable selection on long-term runoff forecasting using local and global climate information - Binlin Yang; Lu Chen; Bin Yi; Siming Li (Journal of Hydrology, 2024)

Regeneration of CO2 from CO2-rich absorbents using hollow fiber membrane contactors in liquid–liquid extraction mode - Siming Chen; Chunjin Zhang; Jingchao Liu (Chemical Engineering Journal, 2024)

Mesoporous carbon hollow spheres based sensitive SPME probes for in vivo sampling analysis of selected plant hormones in Chinese aloes - Yan Liu; Jiajia Han; Guosheng Chen; Siming Huang; Shuyao Huang; Juan Zheng; Jianqiao Xu; Fang Zhu; Gangfeng Ouyang (Analytica Chimica Acta, 2024)

Cinnamaldehyde Alleviates Alveolar Epithelial Cell Injury in ALI by Inhibiting the CaMKII Pathway - Lei Liu; Hao Zhang; Siming Chen; Wankang Dian; Zhou Zheng (Cell Biochemistry and Biophysics, 2024)

MPM simulation of frictional heating–induced hypermobility of landslides - Xiaoqin Lei; Siming He; Xiaoqing Chen; Zongji Yang; Youkou Dong; Liangliang Wang (Landslides, 2024)

Activation of the NLRP3-CASP-1 inflammasome is restrained by controlling autophagy during Glaesserella parasuis infection - Chaoxiong Yue; Jinquan Li; Siming Zhang; Ruyi Ma; Mingjiao Suo; Yiwen Chen; Hui Jin; Yan Zeng; Yushan Chen (Veterinary Microbiology, 2024)

A numerical method to consider the interaction between multiple fractures in frozen rocks based on XFEM - Yun Zhou; Xianjun Tan; Diansen Yang; Weizhong Chen; Zhouzhou Su; Peichao Zheng; Reziwanguli Shataer; Dong Wang; Siming Tian; Wei Wang (Computers and Geotechnics, 2024)

A unified model for frost wedging in an open fissure under unidirectional freezing - Peichao Zheng; Xianjun Tan; Hailiang Jia; Kai Shen; Zhouzhou Su; Yun Zhou; Reziwanguli Shataer; Yi Xie; Dong Wang; Siming Tian; Wei Wang; Weizhong Chen (International Journal of Rock Mechanics and Mining Sciences, 2024)

Oral immunization with recombinant L. lactis expressing GCRV-II VP4 produces protection against grass carp reovirus infection - Huiliang Wu; Jiyuan Yin; Siming Li; Hao Wang; Peng Jiang; Pengfei Li; Zhaoyang Ding; Han Yan; Bo Chen; Linchuan Wang; Qing Wang (Fish & Shellfish Immunology, 2024)

Surface addition of Ag on PbO2 to enable efficient oxygen evolution reaction in pH-neutral media - Siming Li; Meng Shi; Chunxia Wu; Kaiqi Nie; Zheng Wei; Xiaopeng Jiang; Xinbing Liu; Huili Chen; Xinlong Tian; Daoxiong Wu; Yawei Li (Chemical Engineering Journal, 2024)

Enrichment of resistant starch in starch-protein hydrolysate binary matrix by modulating pH during thermal processing - Cuihong Dai; Zihang Cheng; Yanyu Chen; Dongling Qiao; Gaolei Xi; Qiuling Wang; Fan Zhu; Siming Zhao; Binjia Zhang (Food Research International, 2023)

Study on hydrogenation of oxygenated aromatic hydrocarbons via water-gas shift reaction in a subcritical CO-H2O system - Jiale Gu; Huan Li; Wencai Peng; Di Zhu; Jiajia Chen; Shengjie Luo; Siming Liu; Wenxiang Zhao; Youqing Wu; Sheng Huang; Shiyong Wu (Fuel, 2023)

Ingesting retrograded rice (Oryza sativa) starch relieves high-fat diet induced hyperlipidemia in mice by altering intestinal bacteria - Zihang Cheng; Nannan Li; Zhining Chen; Kaikai Li; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Chemistry, 2023)

Genome-resolved metagenomic insight into vanadate and ammonium elimination in sulfur-based autotrophic biosystem - Wenyue Yan; Siming Chen; Min Li; Sitong Liu; Baogang Zhang (Chemical Engineering Journal, 2023)

Electrical stimulation promotes synchronous nitrobenzene bio-degradation and vanadate bio-reduction - Siming Chen; Jin Li; Zongyan Li; Shuo Li; Baogang Zhang (Chemical Engineering Journal, 2023)

Research on the distribution of S species in the pressure oxidation leaching process of SrS solution - Siming Chen; Dongping Duan; Yanjiang Li; Yan Liu; E Zhou (Minerals Engineering, 2023)

The impact of GmTSA and GmALS on soybean salt tolerance: uncovering the molecular landscape of amino acid and secondary metabolism pathways - Minghao Sun; Siming Wei; Jiarui Liu; Luyao Wang; Yu Zhang; Limin Hu; Jingxi Piao; Zhao Liang; Hongwei Jiang; Dawei Xin; Ying Zhao; Qingshan Chen; et al. (Theoretical and Applied Genetics, 2023)

Bioinspired polydopamine nanosheets for the enhancement in anti-corrosion performance of water-borne epoxy coatings - Mingjun Cui; Xinyu Chen; Shixiang Mei; Siming Ren (Chemical Engineering Journal, 2023)

Degradation characteristics of intracellular and extracellular ARGs during aerobic composting of swine manure under enrofloxacin stress - Jiaojiao Xu; Jielan Huang; Longhai Chen; Majian Chen; Xin Wen; Pengfei Zhang; Siming Li; Baohua Ma; Yongde Zou; Yan Wang; Xindi Liao; Yinbao Wu (Chemical Engineering Journal, 2023)

Bioleaching performance of vanadium-bearing smelting ash by Acidithiobacillus ferrooxidans for vanadium recovery - Xiaoxiao Guo; Siming Chen; Yawei Han; Chunbo Hao; Xiujuan Feng; Baogang Zhang (Journal of Environmental Management, 2023)

Development of a HPLC-UV Method for the Separation and Quantification of Hesperidin, Neohesperidin, Neohesperidin Dihydrochalcone and Hesperetin - Lin Chen; Siming Zhu; Chunqing Wang; Liang Chen (Natural Product Research, 2023)

Physicochemical and functional properties of chitosan-based edible film incorporated with Sargassum pallidum polysaccharide nanoparticles - Ke Zhang; Qing Chen; Jie Xiao; Lijun You; Siming Zhu; Chao Li; Xiong Fu (Food Hydrocolloids, 2023)

Mapping and validation of quantitative trait loci associated with dorsal aleurone thickness in rice (Oryza sativa) - Yiwen Xu; Siming Chen; Mingming Xue; Xingyu Chen; Zhibo Liu; Xuefeng Wei; Ji-Ping Gao; Chen Chen (Theoretical and Applied Genetics, 2023)

Global DNA and protein interactomes of FLT1P1 (Fms-related tyrosine kinase 1 pseudogene 1) revealed its molecular regulatory functions associated with preeclampsia - Lu Zhao; Siming Xin; Yunfei Wu; Shaofang Huang; Kangxiang Xu; Yuqi Xu; Dong Ruan; Bingqi Wu; Dong Chen; Xiaoju He (Molecular Biology Reports, 2023)

Statistical optimization of hydrogen production from bio-methanol steam reforming over Ni-Cu/Al2O3 catalysts - Yi-Kai Chih; Wei-Hsin Chen; Siming You; Chun-Han Hsu; Hong-Ping Lin; Salman Raza Naqvi; Veeramuthu Ashokkumar (Fuel, 2023)

Refined-JinQi-JiangTang tablet ameliorates hypertension through activation of FGF21/FGFR1 axis in fructose-fed rats - Siming Li; Xiaoling Li; Jing Fan; Xinhang Jia; Hemeng Wang; Fangxin Dong; Haoyang Mao; Chen Zhang; Wenfei Wang; Ye Jiang; Lijun Yan; Na Zhang (Journal of Natural Medicines, 2022)

Supplementation of Bacillus sp. DU-106 Alleviates Antibiotic-Associated Diarrhea in Association with the Regulation of Intestinal Microbiota in Mice - Darong Huang; Yanlan Chen; Hongzhu Chen; Xinyu Deng; Jianzhao Huang; Siming Lu; Pan Li; Bing Du (Probiotics and Antimicrobial Proteins, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Transcriptomic and histological analysis of exposed facial skin areas wrinkled or not and unexposed skin - Renan Paulo Martin; Patricia Varela; Caio Peres Gomes; Maryana Mara Marins; Rafael Filippelli-Silva; Samira Yarak; Juliana L. M. Soares; Adriana Sanudo; Jolanta Idkowiak-Baldys; Siming Chen; Cheng Hwang; Yong Zhuang; et al. (Molecular Biology Reports, 2022)

A Fusion Approach for Suppression of Environmental Noise in Spread Spectrum Induced Polarization Data - Siming He; Jian Guan; Dachuan Chen; Hang Xu; Yi Wang (Pure and Applied Geophysics, 2021)

Genetic parameters for growth and Quambalaria shoot blight resistance in Corymbia citriodora subsp. variegata - Shengkan Chen; Jianbo Chen; Guanming Yi; Mei Qin; Shiqi Ren; Ziyu Deng; Qinglan Tang; Dongqiang Guo; Yuanli Zhu; Zhangqi Yang; Chonglu Zhong; Siming Gan; et al. (Euphytica, 2021)

UAV-based gully retrogressive erosion status dynamic variability investigations in Chinese Loess Plateau - Huo Aidi; Chen Siming; Peng Jianbing; Cheng Yuxiang (Arabian Journal of Geosciences, 2021)

Northern Hemisphere Sudden Stratospheric Warming and Its Downward Impact in Four Chinese CMIP6 Models - Jian Rao; Siming Liu; Yuanhao Chen (Advances in Atmospheric Sciences, 2021)

Citywide Traffic Analysis Based on the Combination of Visual and Analytic Approaches - Feng Liu; Gennady Andrienko; Natalia Andrienko; Siming Chen; Davy Janssens; Geert Wets; Yannis Theodoridis (Journal of Geovisualization and Spatial Analysis, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Simulation of effects of particle breakage on sliding surface friction for a hypothetical soil continuum moving on an inclined plane - Zheng Chen; Siming He (Landslides, 2020)

Single-cell transcriptome analysis of the novel coronavirus (SARS-CoV-2) associated gene ACE2 expression in normal and non-obstructive azoospermia (NOA) human male testes - Xixi Liu; Yidong Chen; Wenhao Tang; Li Zhang; Wei Chen; Zhiqiang Yan; Peng Yuan; Ming Yang; Siming Kong; Liying Yan; Jie Qiao (Science China Life Sciences, 2020)

Simulating the process of the Jinshajiang landslide-caused disaster chain in October 2018 - Wei Liu; Nengpan Ju; Zhen Zhang; Zheng Chen; Siming He (Bulletin of Engineering Geology and the Environment, 2020)

Enhanced correlations of EST-SSR-based genetic distance with hybrid performance, specific hybridizing ability, and heterosis using effect-increasing and effect-decreasing alleles: a case study in Eucalyptus L’Hér. - Shengkan Chen; Changpin Zhou; Xudong He; Qijie Weng; Fagen Li; Mei Li; Yong Guo; Siming Gan (Tree Genetics & Genomes, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Source characteristics and dynamics of the October 2018 Baige landslide revealed by broadband seismograms - Zhen Zhang; Siming He; Wei Liu; Heng Liang; Shuaixing Yan; Yu Deng; Xiuqiang Bai; Zheng Chen (Landslides, 2019)

Measuring and estimating the impact pressure of debris flows on bridge piers based on large-scale laboratory experiments - Dongpo Wang; Zheng Chen; Siming He; Yang Liu; Hao Tang (Landslides, 2018)

Genotypic Variation and Genotype-by-Environment Interactions in Growth and Wood Properties in a Cloned Eucalyptus urophylla × E. tereticornis Family in Southern China - Heyu Yang; Qijie Weng; Fagen Li; Changpin Zhou; Mei Li; Shengkan Chen; Hongxia Ji; Siming Gan (Forest Science, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

Interaction of Wip1 and NF-κB regulates neuroinflammatory response in astrocytes - Fan Xu; Lifei Chen; Xin Zhao; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li (Inflammation Research, 2017)

Genetic parameters for growth and wood mechanical properties in Eucalyptus cloeziana F. Muell. - Changrong Li; Qijie Weng; Jian-Bo Chen; Mei Li; Changpin Zhou; Shengkan Chen; Wei Zhou; Dongqiang Guo; Cuixiang Lu; Jian-Cheng Chen; Dongyun Xiang; Siming Gan (New Forests, 2017)

Up-regulation of Wip1 involves in neuroinflammation of retinal astrocytes after optic nerve crush via NF-κB signaling pathway - Haibin Zhong; Ling Cui; Fan Xu; Lifei Chen; Li Jiang; Hui Huang; Jiping Xu; Xin Zhao; Li Li; Siming Zeng; Min Li (Inflammation Research, 2016)

CD200Fc reduces TLR4-mediated inflammatory responses in LPS-induced rat primary microglial cells via inhibition of the NF-κB pathway - Li Jiang; Fan Xu; Wenjing He; Lifei Chen; Haibin Zhong; Yu Wu; Siming Zeng; Li Li; Min Li (Inflammation Research, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Up-regulation of SKIP relates to retinal ganglion cells apoptosis after optic nerve crush in vivo - Yu Wu; Fan Xu; Hui Huang; Lifei Chen; Meidan Wen; Li Jiang; Lu Lu; Li Li; Di Song; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Upregulation of Gem relates to retinal ganglion cells apoptosis after optic nerve crush in adult rats - Fan Xu; Hui Huang; Yu Wu; Lu Lu; Li Jiang; Lifei Chen; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Erratum to: Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)

Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)